Location Choice Model for distribution centers: for use in regional economic centers - Silva, Joselma Maria da; Júnior, Djalma Silva Guimarães; Sant'Anna, Carlos Henrique Michels de (Revista Gestão da Produção Operações e Sistemas, 2021)
Purpose - This paper aims to propose a location choice model to establish distribution centers using linear programming. Design/methodology/approach - Locational choice models allow decision makers to select between different possible locations, based on the best fit of established criteria. For this, a Mixed-Integer Linear Programming model (MILP) was proposed to identify the most efficient location for a distribution center in the region in the Mata Norte of the State of Pernambuco, Brazil. Findings - The MILP model allowed us to identify the factors that support transport cost minimization, which are significant for the distribution logistics, indicating a location that minimizes these costs and generates greater efficiency in the logistics in a region within the interior of the state, which is a regional economic center. Originality/Value - Most location choice models for distribution centers are built on the logic of densely populated regions and large urban centers, the value of this study lies in its attempt to optimize the efficiency of logistics within inland regions. Keywords - Locational decision. Linear programming. Logistics. Distribution centers. Local economy.